Improving the integration of wind power generation into AC microgrids using flywheel energy storage - Suvire, Gaston Orlando (2017)
The connection of wind power generation into ac microgrids (MGs) is steadily increasing. This incorporation can bring problems onto the power quality and dynamics of the electrical grid due to the lack of controllability over the wind. In this work, a flywheel energy storage (FES) is used to mitigate problems introduced by wind generation into MGs. A dynamic model of the FES device is briefly presented and a technique to control the power exchanged between the device and the power system is proposed. The control technique has three modes, namely: voltage control (VC), frequency control (FC), and active power stabilization (APS). Simulation tests on the behavior of the FES device are analyzed when it works in combination with wind generation in the electrical microgrid. Results show an acceptable performance of the proposed control techniques along with a high effectiveness to smooth the active power fluctuations of wind generation. © 2010-2012 IEEE.